2018
DOI: 10.1371/journal.pone.0194180
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the inFLUenza Patient-Reported Outcome (FLU-PRO) diary in patients with influenza-like illness (ILI)

Abstract: BackgroundThe inFLUenza Patient Reported Outcome (FLU-PRO) measure is a daily diary assessing signs/symptoms of influenza across six body systems: Nose, Throat, Eyes, Chest/Respiratory, Gastrointestinal, Body/Systemic, developed and tested in adults with influenza.ObjectivesThis study tested the reliability, validity, and responsiveness of FLU-PRO scores in adults with influenza-like illness (ILI).MethodsData from the prospective, observational study used to develop and test the FLU-PRO in influenza virus posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Clinical symptoms were assessed using the FLU-PRO Symptom Severity Assessment Tool, a participant-directed questionnaire designed to assess influenza disease severity that has been validated in both natural infection and influenza challenge studies [39][40][41] . In addition, a physician assessment was also performed daily for 10 days to determine the presence or absence of influenza signs/symptoms.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Clinical symptoms were assessed using the FLU-PRO Symptom Severity Assessment Tool, a participant-directed questionnaire designed to assess influenza disease severity that has been validated in both natural infection and influenza challenge studies [39][40][41] . In addition, a physician assessment was also performed daily for 10 days to determine the presence or absence of influenza signs/symptoms.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Prior analyses of the FLU-PRO in patients with and without influenza have shown that changes in item scores of ,0.5 are not clinically meaningful. 10,28 The "ability to detect change" assessment evaluates the sensitivity of a PRO instrument in detecting clinically important changes in patients' health conditions. In this study, the ability of the FLU-PRO to detect change was assessed by summarizing the RSV participant's average change from baseline in daily symptom scores at illness weeks 1 to 3 and comparing it with minimal clinically significant changes.…”
Section: Methodsmentioning
confidence: 99%
“…The large sample size (N = 1268) resulted in statistical significance for small differences that were not clinically meaningful (ie, smaller than the minimal clinically significant change determined by both distribution-based and anchoredbased methods). 10,28 The FLU-PRO's ability to detect change was demonstrated: all symptom score changes, except for earache and gastrointestinal symptoms, were clinically meaningful in week 1 of illness (Fig. 1).…”
Section: Test-retest Reliability Ability To Detect Change and Convementioning
confidence: 97%
See 2 more Smart Citations